lPenerapan Metode TOPSIS Dalam Sistem Pendukung Keputusan Rekomendasi Program Studi Perguruan Tinggi - Evita Setyaningrum; Agyztya Premana; Puji Wahyuningsih (IKRA-ITH Informatika : Jurnal Komputer dan Informatika, 2026)
Choosing a study program is an important decision for students before pursuing higher education. Limited information about study programs and a lack of self-understanding often make it difficult for students to select a suitable program. This study aims to provide study program recommendations based on students’ academic and non-academic abilities using the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method. The criteria used in this study include grade point average, supporting subject scores, achievements, and student skills. The alternatives consisted of ten study programs at Universitas Muhadi Setiabudi. The TOPSIS method was applied through decision matrix construction, normalization, weighted normalization, determination of positive and negative ideal solutions, distance calculation, and preference value calculation. The results showed that the Indonesian Language and Literature Education Program (PBSI) obtained the highest preference value of 0.83, followed by the Elementary School Teacher Education Program (PGSD) with 0.70 and Agribusiness with 0.62. These findings indicate that the TOPSIS method is capable of providing objective and measurable study program recommendations based on predetermined criteria, thereby assisting students in selecting study programs that match their potential. Keyword : Decision Support System, TOPSIS, Study Program Recommendation, Higher Education, Decision Making.